Inovasi Rak Pengering Sistem Knockdown Dalam Upaya Penguatan Kualitas Kopi Gayo Sebagai Produk Unggulan Daerah - Indra Mawardi; Hanif; Jannifar; Safaruddin; Zainal Abidin (Ilin Institute, 2020)
The aim of the PKM program is to strengthen the quality and increase the quantity of green been Gayo coffee through the implementation of a drying rack innovation with a knockdown system. Methods for solving problems using structural and functional methods. The structural method is in the form of designing and fabricating the knockdown drying rack system, while the functional approach method is carried out in the form of problem identification, implementation and training, to mentoring. The output of this activity has been produced in the form of a knockdown coffee drying rack. The knockdown system innovation on coffee drying racks has many advantages over conventional drying racks. The use of knockdown drying racks has increased the dry coffee bean production capacity by up to 40% and the quality of the coffee beans is well maintained.